Plataforma digital que conecte responsables del hogar con técnicos de servicios del hogar - Navarro Rossel, Omar Humberto (2019)
Nowadays, there are digital media providers/platforms that allow homeowners to look for service technicians to help them in jobs such as painting, maintenance, cleaning or remodeling. However, the use of these platforms presents difficulties and are hardly used by users mainly because they don’t focus on household services, they are not user friendly, they seem unreliable or they have outdated information. In addition, there are some service technicians who even pay a monthly subscription to use these platforms but do not obtain desired results, causing the need to stick to traditional ways to contact customers. These traditional ways of obtaining leads demand effort and money and range from standing outside markets and housing complexes to investing in flyers and signs that are posted or hanged on public poles and/or sidewalks. Based on the above, the idea arises of developing a mobile application whose main objective is to connect the community of household managers with the community of service technicians. Allowing household members to find and contact a technician in a quick and easy way, supporting the technician selection process through reviews and experiences from other users, as well as the constant evaluation of the indicators generated by the platform in order to give them the best options at all times. On the other hand, the application will allow the technicians to access greater job opportunities due to the rotation algorithm (qualification algorithm and SEO / PPC rotation algorithm), which will process different variables such as users reviews, time spent on conversion , number of accepted or rejected offers, complaints, among others. It is important to note that trust between both communities, users and providers, is the main axis for the success of the proposed platform, as seen on other successful on demand or collaborative platforms such as Uber, Airbnb, etc. For this reason, the use of algorithms such as the one previously mentioned along with the constant improvement of the platform focused on user satisfaction for both ends, providers and household members, is a key factor on the long-term feasibility of the proposed mobile app.